Numerical investigation of added resistance and wave pattern on a planing vessel in regular head waves. (2018) - Safari, Ali; Nikseresht, Amir H.
In recent years, a great deal of research effort on ship hydrodynamics is devoted to practical navigation problems in moving planing vessels safety. The purpose of this study is to investigate the added resistance of DTMB 62 model 4667-1 planing hull using a CFD software based on the finite volume method to solve the RANS equations in different Fr numbers in head waves. In addition, the wave profile and wave pattern on the hull of the vessel is investigated. For this purpose, a finite volume ANSYS-FLUENT code is used to solve the Navier-Stokes equations for simulating the flow field around the vessel. In addition, an explicit VOF scheme and k-ε model is used to capture the interface and to model the turbulence respectively. The results show that increasing the Froude number, increases the added resistance of a planing vessel in regular waves.